The clinical epidemiology of sickle cell anemia In Africa - Macharia, AW; Mochamah, G; Uyoga, S; Ndila, CM; Nyutu, G; Makale, J; Tendwa, M; Nyatichi, E; Ojal, J; Shebe, M; Awuondo, KO; Mturi, N; et al. (Wiley, 2017)
Sickle cell anemia (SCA) is the commonest severe monogenic disorders of humans. The disease has been highly characterized in high-income countries but not in sub-Saharan Africa where SCA is most prevalent. We conducted a retrospective cohort study of all children 0-13 years admitted from within a defined study area to Kilifi County Hospital in Kenya over a five-year period. Children were genotyped for SCA retrospectively and incidence rates calculated with reference to population data. Overall, 576 of 18,873 (3.1%) admissions had SCA of whom the majority (399; 69.3%) were previously undiagnosed. The incidence of all-cause hospital admission was 57.2/100 person years of observation (PYO; 95%CI 52.6-62.1) in children with SCA and 3.7/100 PYO (95%CI 3.7-3.8) in those without SCA (IRR 15.3; 95%CI 14.1-16.6). Rates were higher for the majority of syndromic diagnoses at all ages beyond the neonatal period, being especially high for severe anemia (hemoglobin < 50 g/L; IRR 58.8; 95%CI 50.3-68.7), stroke (IRR 486; 95%CI 68.4-3,450), bacteremia (IRR 23.4; 95%CI 17.4-31.4), and for bone (IRR 607; 95%CI 284-1,300), and joint (IRR 80.9; 95%CI 18.1-362) infections. The use of an algorithm based on just five clinical features would have identified approximately half of all SCA cases among hospital-admitted children with a number needed to test to identify each affected patient of only fourteen. Our study illustrates the clinical epidemiology of SCA in a malaria-endemic environment without specific interventions. The targeted testing of hospital-admitted children using the Kilifi Algorithm provides a pragmatic approach to early diagnosis in high-prevalence countries where newborn screening is unavailable.